Intergenerational Power Shift and the Rise of Non-arranged Marriages among Refugees - Andrew Foster; Merve Betül Gökçe; Murat G. Kirdar (Institute of Labor Economics (IZA), 2023)
The experience of war and refugee status can alter intra-family dynamics and therefore have implications for family formation, including marriage. This study investigates marriage patterns among Syrian refugees in Turkey. Utilizing the nationally representative 2018 Turkey Demographic Health Survey (TDHS), we conduct a duration analysis of marriage outcomes among Syrian refugees in Turkey—tracking women throughout their residence in prewar Syria, postwar Syria, and Turkey. We find that early marriage is more prominent among refugees who were unmarried at the time of migration than those married before migration; the mean marriage age drops from 19.6 in prewar Syria to 19.1 in postwar Syria and 18.1 in Turkey. Using the TDHS and prewar Syrian surveys, we show that this finding aligns with the observed declines in household income and young women's opportunity cost of marriage. Our duration analysis also reveals a notable shift from traditional arranged marriages to more modern forms among refugees in Turkey. An intergenerational power shift may drive the shift toward non-arranged marriages. After arrival in Turkey, parental wealth and employment decline. In contrast, Syrian youth have higher age-adjusted employment rates than in prewar Syria. Moreover, for demographic groups with stronger intergenerational power shifts, non-arranged marriages increase more.
Keywords: J12; J15; 330; Syrian refugees; forced migration; arranged marriage; generational power transitions; Turkey